Pertumbuhan Tanaman Pakchoy (Brassica chinensis L.)pada Tanah Gambut dengan Pemberian Pupuk Kompos Kotoran Kambing - Rahmawati, Maurilla Illa, Mukarlina (Universitas Tanjungpura, 2017)
The cultivation of pakchoy (Brassica chinensis L.) on peat soil is challenged by a low soil fertility. The addition of goat manure compost is expected to increase the growth of pakchoy and the quality of the soil. The aim of the research were to identifying the infleunce of goat manure compost towards the growth of pakchoy (B. chinensis L.) on the peat soil. Additionally, it attempts to study the lowest concentrational of goat manure compost which can provide the best result for the growth of pakchoy (B. chinensis L.) on the peat soil.The research was conducted in a green house and a biology lab oot of the faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak. The analysis of soil, compost, leaf area and lime needs were carried out in an agronomy lab and chemical and soil fertility lab since October 2016 to March 2017. The research employed a completely randomised design (CRD) with a four-lewel treatment, including P0= 0 (control), P1= 62,5 gram, P2= 97,5 gram, and P3= 125 gram. The data in this research was then analysed through ANOVA test (Analysis of Variance). The result of ANOVA test which provides a clear influence was continued by a Duncan test at the level of 5%. The result showed that the provision of goat manure compost provides a clear effect toward all growth parameters. Moreover, the compost concentration on 62.5 gram is the lowest concentration which can provide the best result towards the plant height by 19.13 cm, number of leaves by 8.67 cm, total leaf area by 291.5 cm2, gross weight by 17.71 gram and dry weight by 1.22 gram.